Pengaruh Kompensasi Dan Pengawasan Terhadap Disiplin Kerja Pegawai Pada Dinas Cipta Karya Dan Tata Ruang Kabupaten Kutai Kartanegara - Syahruddin Syahruddin (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract :Office of Human Settlements and Spatial Kutai district is one of the local government agency that has the task of carrying out the authority of decentralization and deconcentration tasks in the field of Human Settlements, Spatial and Hygiene management, and Cemetery which is located street Wolter Monginsidi, Building ULP. Regent Office complex with the Head of Department Mr. H. Basrie Hasan ST., MT. the number of employees as many as 127 employees. The aim of this study was to apply the knowledge gained during this field and for the world to know and how much influence Compensation and Supervision influence the Work Discipline Employees At the Department of Human Settlement and Spatial Kutai district. Variable compensation and oversight together (simultaneously) be able to demonstrate its impact on employee discipline. The first hypothesis stated "Allegedly Compensation and Monitoring significantly affect Employees At Work Discipline Office of Human Settlements and Spatial Kutai regency" accepted and proven true. From the second partial correlation test results above shows that the value of the variable control than variable compensation, so that the control variable is the variable most dominant influence on employee discipline. From the description, it can be concluded that the second hypothesis in this study "It is believed that compensation Dominant Against Influential Work Discipline Employees at the Office of Human Settlements and Spatial Kutai regency" accepted and proven true.Keywords: Compensation, Control, Discipline